Competition and Capitalization, As Controlled by the Massachusetts Gas Commission - Gray, John H. (Quarterly Journal of Economics, 1901)
Journal Article Competition and Capitalization, as Controlled by the Massachusetts Gas Commission Get access John H. Gray John H. Gray Northwestern University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 15, Issue 2, February 1901, Pages 254–276, https://doi.org/10.2307/1884896 Published: 01 February 1901